PsycEXTRA Dataset 2011
DOI: 10.1037/e525432012-001
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Health Administration Mental Health Program Evaluation: Capstone Report

Abstract: The R AND Corporation is a nonprofit institution that helps improve policy and decisionmaking through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. R ® is a registered trademark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 75 publications
(63 reference statements)
1
58
1
Order By: Relevance
“…Similarly, the other mixed health care example, the HSE, has accessibility and appropriateness as their main focus areas for KPIs. The public health care examples of the NHS and VHA differ in their main performance metrics in that for the NHS, efficiency and accessibility are mainstays whereas the VHA is fairly balanced across all dimensions, but is missing KPIs for efficiency (Table 1); though some of the KPIs used by VHA may also infer efficiency (Watkins & Pincus, 2011). However, the provided -10 -definitions of those KPIs do not meet this study's criteria for being a KPI, which represents the efficiency domain as outlined in Table 3.…”
Section: Use In Practice: Comparing Application Across Specific Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the other mixed health care example, the HSE, has accessibility and appropriateness as their main focus areas for KPIs. The public health care examples of the NHS and VHA differ in their main performance metrics in that for the NHS, efficiency and accessibility are mainstays whereas the VHA is fairly balanced across all dimensions, but is missing KPIs for efficiency (Table 1); though some of the KPIs used by VHA may also infer efficiency (Watkins & Pincus, 2011). However, the provided -10 -definitions of those KPIs do not meet this study's criteria for being a KPI, which represents the efficiency domain as outlined in Table 3.…”
Section: Use In Practice: Comparing Application Across Specific Systemsmentioning
confidence: 99%
“…Establishing a collaborative process is integral in the development of KPIs as MESUD academics, clinicians, consumers and decisionmakers will differ in their opinion of what KPIs are of most importance (Waraich et -11 -al., 2010). The structured consensus is ultimately the most rigorous development method for KPIs; however, this, in itself, requires sufficient resources and infrastructure to execute, such that it is the least used development method for MESUD KPIs (Lauriks et al, 2012;Waraich et al, 2010;Watkins & Pincus, 2011).…”
Section: Development and Content Of Kpis For Mesudsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not part of the systematic review because it was not published in the peerreviewed literature, an Altarum/RAND study of VA quality of care for mental health conditions (Sorbero et al, 2010;Watkins et al, 2011) showed that VA care performed significantly better than the private plans on assessment measures and medication-management measures. The private plans exhibited significantly higher rates of engagement for two measures related to treatment for substance use disorders.…”
Section: Effectiveness Of Care In Va Compared With Non-vamentioning
confidence: 99%